Information literacy in the Communication Sciences career, Universidad San Gregorio de Portoviejo - Cedeño Espinoza, Ricardo David (2023)
An investigation is presented whose objective is to diagnose the informational competences of the students of the Communication Sciences career at the San Gregorio University, in Portoviejo. A descriptive study was carried out, with a quantitative approach, applying the documentary analysis method in the bibliographic review on the subject and the survey technique, considering the validated ALFIN-HUMASS questionnaire, which was applied to all the students of the career. The results denote that, although students generally recognize the importance of informational skills, they self-identify with low levels of sufficiency; especially in the elements of treatment and evaluation of information. As conclusions, it is stated that all the categories of informational competencies analyzed require your attention to implement informational literacy actions from the university library and thus achieve high levels of self-efficacy in the use of information.